Study on Number of Electrodes Programmed and Place of Stimulation in Cochlear Implant Patients - Iida, Masahiro; Sakai, Makoto; Kitano, Yoko; Ishida, Katsunori; Koga, Keijiro; Naito, Akira (AUDIOLOGY JAPAN, 1999)
The study was conducted to clarify the effects of reduction of the number of electrodes programmed, and that of changing the area in cochlear stimulated on the speech perception performance in 6 cochlear implant patients. Subjects were adult cochlear implant programming where all 22 electrodes were usable. Speech perception performance was evaluated by reducing the number of electrodes programmed from 20 to 10, to 7, to 5 as well as by changing the stimulation area and ranges with 10 channels in use. The results showed that even when the number of channels was decreased by half to 10 (every other electrode stimulated), there was no obvious decline of speech perception performance observed whereas the speech perception abilities tended to go down when the stimulation range was narrowe within the cochlea.